Apoyo familiar a jóvenes en proceso de rehabilitación por consumo spa, desde su experiencia (2022)
The objective of this research is to understand from the experience of young people in the process of rehabilitation for PAS consumption, the support received from families in the NISSI foundation, located in the city of Manizales, department of Caldas, Colombia. By means of a qualitative and interpretative research, which was carried out with 7 participants between 20 and 25 years of age.